Extreme slow growth as alternative strategy to survive deep starvation in bacteria - Declan A. Gray (Nature Portfolio, 2019)
Bacteria can become dormant or form spores when starved for nutrients. Here, Gray et al. describe an alternative strategy, or ‘oligotrophic growth state’, showing that non-sporulating Bacillus subtilis cells can survive deep starvation conditions by adopting an almost coccoid shape and extremely low growth rates.